Fumonisin B1: A Tool for Exploring the Multiple Functions of Sphingolipids in Plants - Zeng, Hong-Yun; Li, Chun-Yu; Yao, Nan (Frontiers in Plant Science, 2020)
Fumonisin toxins are produced by Fusarium fungal pathogens. Fumonisins are structural analogs of sphingosine and potent inhibitors of ceramide synthases (CerSs); they disrupt sphingolipid metabolism and cause disease in plants and animals. Over the past three decades, researchers have used fumonisin B1 (FB1), the most common fumonisin, as a probe to investigate sphingolipid metabolism in yeast and animals. Although the physiological effects of FB1 in plants have yet to be investigated in detail, forward and reverse genetic approaches have revealed many genes involved in these processes. In this review, we discuss the intricate network of signaling pathways affected by FB1, including changes in sphingolipid metabolism and the effects of these changes, with a focus on our current understanding of the multiple effects of FB1 on plant cell death and plant growth. We analyze the major findings that highlight the connections between sphingolipid metabolism and FB1-induced signaling, and we point out where additional research is needed to fill the gaps in our understanding of FB1-induced signaling pathways in plants.